2011
DOI: 10.1007/s00383-011-2912-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the pediatric surgery match: factors predicting outcome

Abstract: Applicant variables associated with success in the match included quality of letters, number and type of publications, research experience, graduation from a US medical school, and AOA membership. Factors not correlated with outcome included advanced degrees (PhD, Masters), other fellowship training, and community-based versus university-based residency training. Logistic regression analysis demonstrated no independent factors for overall match success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Other studies have observed an inconsistent effect of gender (female) on the likelihood of matching to residency programs among nonpharmacy health care disciplines. Although de Oliveira et al found similar results with applicants pursuing an anesthesiology residency, 11 other medical disciplines -including ophthalmology, 12 otolaryngology-head and neck surgery, 13 plastic surgery, 14 pediatric surgery, 15 and pediatric dental 16 17 Keshishian also found gender-based differences. 18 Regarding influences on students' selection of pharmacy as a major, female students were more likely than males to select "desire to help others" as a strong motivating factor to pursing a pharmacy career.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Other studies have observed an inconsistent effect of gender (female) on the likelihood of matching to residency programs among nonpharmacy health care disciplines. Although de Oliveira et al found similar results with applicants pursuing an anesthesiology residency, 11 other medical disciplines -including ophthalmology, 12 otolaryngology-head and neck surgery, 13 plastic surgery, 14 pediatric surgery, 15 and pediatric dental 16 17 Keshishian also found gender-based differences. 18 Regarding influences on students' selection of pharmacy as a major, female students were more likely than males to select "desire to help others" as a strong motivating factor to pursing a pharmacy career.…”
Section: Discussionmentioning
confidence: 89%
“…Future studies should consider assessing the influence of the reputation of pharmacy schools and residency programs on the likelihood of a candidate matching to a residency program. 15 …”
Section: Resultsmentioning
confidence: 99%
“…Pursuit of fellowship in pediatric surgical critical care has evolved as an attractive alternative for residents interested in pediatric surgery careers. While other studies have examined factors predictive of matching in pediatric surgery [2][3][4]6], no other published study has reported on the fellowship experiences and career paths of PSCCF graduates.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have noted a gradual shift away from a perceived mandatory two-year basic science research track, once essentially expected among successful applicants [2][3][4][5]. Pursuit of fellowship in pediatric surgical critical care has evolved as an attractive alternative for residents interested in pediatric surgery careers.…”
Section: Discussionmentioning
confidence: 97%
“…Many spend time in a laboratory for the sole purpose of securing a pediatric surgical fellowship. Indeed, several studies spanning two decades have verified that the number of publications and research experience remain strong predictors of success in the pediatric surgical match (45,46,47). I would argue that this is a very important component of surgical resident training.…”
Section: Adaptation For Success In Career Developmentmentioning
confidence: 99%